Three-dimensional guidance control for vehicle convoy and interception - Yihua Dong; Yuefen Tan; Jingang Zhao; Wencheng Wang (Automatika)
In the 3-D space, this paper implements vehicle convoy and interception by using guidance strategy. Based on the differential equations for the range, the pitch angle and the yaw angle between successive vehicles, the deviated pursuit and the proportional navigation are proposed to derive decentralized control strategy for vehicle convoy and interception control. Guidance laws are used for convoy and interception, and this method presents a family of navigation laws resulting in a rich behaviour for different parameters. Convoy and interception performance of the proposed guidance laws is superior to the pure proportional navigation (PPN). Simulations are proposed to demonstrate the feasibility and effectiveness of the proposed control method.